Low-cost system for the management of portable basic clinical information, through the use of rfid technologies - Auccahuasi, Wilver (2020)
ABSTRACT Information and communication technologies are causing a positive impact on people's lives, from communication through mobile devices, which can also be used in multiple applications, such as educational, recreation, among others. One of the areas where it is causing a greater impact is health, because of how important the use of technology is both in diagnosis and treatment, it could be said that in health systems, technology is your best ally, In the present work, a low-cost system is proposed for the management of basic and necessary clinical information, which can be a determining factor in the preservation of the person's life. There are certain factors that can help maintain people's lives in an emergency, such as blood type, if you are allergic to a certain medication, if you have a heart problem, diabetes problems, knowing your personal information, this Information must always be available and at all times. As a result of this research, it is to present a protocol for the management of this information that everyone can carry either as an identification card or as a key ring. What can be decisive in emergency cases.